Associations between common genetic variants in microRNAs and Hirschsprung disease susceptibility in Southern Chinese children - Wu, Qi (J Gene Med, 2021)
INTRODUCTION: Hirschsprung disease (HSCR), characterized by the defective migration of enteric neural crest cells, is a severe congenital tract disease in infants. Its etiology is not clear at present, although a genetic component plays an important role in its etiology. Many studies focused on the polymorphisms of microRNA (miRNA) in several disease progressions have been reported, including HSCR. However, the findings remain inconclusive. The present study aimed to explore the association of genetic variants in miRNAs and HSCR susceptibility in Southern Chinese children. METHODS: Five single nucleotide polymorphisms (SNPs) (miR‐146A rs2910164, miR‐4318 rs8096901, miR‐3142 rs2431697, miR‐3142 rs2431097 and miR‐3142 rs5705329) were included to be genotyped in the stratified analysis through the Mass ARRAY iPLEX Gold system (Sequenom, San Diego, CA, USA) conducted on all the samples, comprising 1470 cases and 1473 controls. After quality control, the minor allele frequency was compared in cases and controls to analyze the association between SNPs and HSCR using PLINK 1.9 (https://www.cog‐genomics.org/plink) and multiple heritability models were tested (additive, recessive and dominant models). RESULTS: Our results indicated that miR‐4318 rs8096901 polymorphisms were associated with HSCR susceptibility in Southern Chinese children, especially in short‐segment HSCR (S‐HSCR) patients after stratified analysis. CONCLUSIONS: In summary, we report that miR‐4318 rs8096901 was associated with HSCR, especially in SHSCR patients.